2007
DOI: 10.1038/sj.icb.7100125
|View full text |Cite
|
Sign up to set email alerts
|

Normal proportion and expression of maturation markers in migratory dendritic cells in the absence of germs or Toll‐like receptor signaling

Abstract: Dendritic cells (DCs) play major roles in immunosurveillance. In peripheral tissues, 'immature' DCs are dedicated to capturing antigens. Detection of pathogens through Toll-like receptors (TLRs) triggers DC migration to the lymph nodes (LNs), where they acquire a 'mature' phenotype specialized at presenting antigens. However, DCs migrate from tissues and mature even in the absence of overt infections. This has been attributed to detection of commensal flora in the skin, the gut or other peripheral tissues in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 38 publications
9
69
0
Order By: Relevance
“…Although compounds derived from the microbiota influence immune homeostasis in both MyD88-dependent and -independent manners (41, 42), we show in this work that mesenteric lymph from germ-free mice contains a normal proportion of DCs, and that treatment of conventionally housed WT mice with broad-spectrum antibiotics has no effect on the accumulation rate of intestinal CD103 + DCs in the MLN. These results are in agreement with previous observations of similar phenotype and function of DCs in MLN of germ-free and conventionally housed rodents (31,43,44), and collectively argue against a direct role for the gut microbiota in driving the MyD88-dependent steady-state migration of SI LP CD103 + DCs. It still, however, remains possible that TLR ligands present in the food and/or produced by enteric viruses could account for the MyD88 dependency in this process.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although compounds derived from the microbiota influence immune homeostasis in both MyD88-dependent and -independent manners (41, 42), we show in this work that mesenteric lymph from germ-free mice contains a normal proportion of DCs, and that treatment of conventionally housed WT mice with broad-spectrum antibiotics has no effect on the accumulation rate of intestinal CD103 + DCs in the MLN. These results are in agreement with previous observations of similar phenotype and function of DCs in MLN of germ-free and conventionally housed rodents (31,43,44), and collectively argue against a direct role for the gut microbiota in driving the MyD88-dependent steady-state migration of SI LP CD103 + DCs. It still, however, remains possible that TLR ligands present in the food and/or produced by enteric viruses could account for the MyD88 dependency in this process.…”
Section: Discussionsupporting
confidence: 82%
“…Although the proportion of CD205 + CD8a 2 cells among total MLN DCs has been shown to be comparable between MyD88 2/2 and WT mice (31), flow cytometry analysis of MHC-II high DCs revealed that the CD205 + CD8a 2 phenotype does not fully encompass all migratory DCs in the MLN (Supplemental Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…pDC, similar to committed precursors of classical DC, enter lymphoid organs directly from the blood through the high endothelial venules [13][14][15]. Under homeostatic conditions, pDC also inhabit mucosal tissues and organs, albeit at low numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a role in the maintenance of tolerance to skin-derived self-proteins, each of the five identified skin DC subsets migrate to CLN in the absence of inflammation [10,15]. In steady-state CLN, skinderived DC express levels of MHC class II (MHCII) molecules and of costimulatory molecules (CD86 and CD40) that are as high as those found on skinderived DC that reach CLN under inflammation [4,16].…”
mentioning
confidence: 87%
“…29 Importantly, both of the lymph node immigrant subsets are activated upon entering the lymph node, most likely in response to stimuli encounter in the peripheral tissue. 30 This enables examination of autophagy components in cross-presenting (CD103 C ) and noncross-presenting (CD103 ¡ ) DC activated without external intervention. CD103 C DC freshly isolated from skin-draining lymph nodes displayed many more SQSTM1 aggregates per cell than CD103 ¡ DC or CD8 C DC isolated from the same lymph nodes (Fig.…”
Section: Resultsmentioning
confidence: 99%